Disturbances in psychological functions of workers occupationally exposed to styrene. - Lindström, Kari; Härkönen, Hannu; Hernberg, Sven (Scandinavian Journal of Work, Environment & Health, 1976)
The relationship between long-term occupational styrene exposure and disturbances in psychological functions was studied. The exposed group consisted of 98 male workers exposed to styrene in the manufacture of polyester plastic products, and the comparison group comprised 43 concrete reinforcement workers. The duration of exposure in years and the mean mandelic acid concentration in urine (five determinations during 5 weeks before the clinical examination) and the cumulative dose of exposure were used as the indicators of exposure. The psychological functions studied were intelligence, visuomotor speed, visuomotor accuracy, memory, vigilance, and psychomotor performance. Some personality test variables were also included. In a group comparison two variables (visuomotor inaccuracy and poor psychomotor performance) out of 20 showed statistically significant differences and characterized the styrene exposed group. These findings were confirmed when workers with low and high styrene exposure were compared. One variable measuring visuomotor speed and another measuring visual memory were related to the duration of exposure (R = 0.28, p less than 0.05). In a multiple regression analysis disturbances in visuomotor accuracy, poor psychomotor performance, and lowered vigilance proved to have some connection with a high mandelic acid concentration (R = 0.49, p less than 0.01). In addition workers with disturbances in visuomotor accuracy and slight disturbances in virumotor speed had higher mandelic acid concentrations when compared with those workers without any deterioration. The results indicate that disturbances in visuomotor accuracy and, to a lesser degree, in psychomotor performance are the main findings measured by test methods used in this study and related to one indicator of styrene exposure, mandelic acid concentration. The psychological methods used revealed subclinical symptoms related to exposure, and they should aid in making group diagnoses, e.g., when additional information is needed for the determination of the threshold limit value. The deterioration found in visuomotor accuracy could be related to lowered safety in work and traffic.
Keywords: disturbance; mandelic acid; mandelic acid excretion; occupational exposure; polyester plastic; psychological function; styrene; styrene exposure; worker